„Off-label“-Anwendung in der Klinik – Welche Folgen hat ein Urteil des Bundessozialgerichts für die Pädiatrie? - Rascher, Wolfgang; Wimmer, Stefan; Neubert, Antje; Berner, Reinhard; Boos, Joachim; Erdlenbruch, Bernhard; Kaufmann, Jost; Mentzer, Dirk; Pabel, Helmut; Scherer, Sabine; Schwab, Matthias; Wagner, Norbert; et al. (Monatsschrift Kinderheilkunde, 2020)
The off-label prescription of medicines is becoming increasingly more problematic in pediatric and adolescent medicine. A legally binding judgment of the Federal Social Court (BSG) in 2016 has determined under which prerequisites statutory health insurance companies (GKV) can reimburse off-label prescription in inpatient care. It is to be expected that in future the medical service of the health insurance companies (MDK) will inspect the off-label prescription of expensive drugs for which an additional fee is paid and consequently the hospitals face the risk that reimbursement will be denied. The judgement of the BSG also has consequences for the development of guidelines. The aim of the article is the presentation of five supreme court judgments of German courts (1990–2016) on off-label use and the consequences and possible solution approaches for pediatrics. Although most court decisions involve adult medicine, the judgments affect the prescription of medicines for children.
CRIS-Team Scopus Importer:2020-02-28
Keywords: Approval; Children; Court; Guidelines; Medication; Off label use